Determination of Economic Growth, Human Development Index, and Open Unemployment Rate on Poverty Level in the Province of the Special Region of Yogyakarta - Melfiya Rosita; Niniek Imaningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
As one of the provinces that has special features and is nicknamed as a student city, DI Yogyakarta still ranks first with the highest poverty rate on Java Island. Therefore, this study aims to determine the factors that influence the high poverty rate in the Special Region of Yogyakarta Province. Quantitative analysis with the Multiple Linear Regression method is used in this study to determine the effect of each variable. The results of the study show that in the Special Region of Yogyakarta Province in 2009-2023, Economic Growth and Open Unemployment Rate have no effect on the Poverty Rate, while the Human Development Index has an effect on the Poverty Rate in the Special Region of Yogyakarta Province.